The last battle - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 1994)
Jill and Eustace help fight the great last battle in Narnia after a false, cruel leader deceives the people into believing he is Aslan.
Christian Library Journal starred.
Kirkus Review.
Library Journal.
5.8
5-8
Keywords: Fantasy; Fantastic fiction